Motivational Factor Analysis in Indonesian Language Course Selection: PCA Study of Southeast Asian Studies Students at the Open University of Ho Chi Minh City - Erika Firdayanti; Arif Setiawan; Nguyen Thi Thu Hang (UIN Raden Mas Said Surakarta, Indonesia, 2026)
The selection of Indonesian language courses in non-language study programs is often treated as a curricular obligation, resulting in limited understanding of the underlying motivational structure. This lack of empirical mapping may lead to ineffective curriculum design and learning strategies. Therefore, this study aims to identify and analyze the motivational factors influencing the selection of Indonesian language courses among Southeast Asian Studies students at the Open University of Ho Chi Minh City using Principal Component Analysis (PCA). This study employed a quantitative approach with an exploratory factor analysis design. Data were collected through a closed-ended questionnaire administered to 33 B1-level BIPA students. Data analysis involved testing sampling adequacy (KMO), Bartlett’s Test of Sphericity, extraction of principal components, and factor rotation to identify latent motivational structures. The findings reveal that students’ motivation is multidimensional and relatively balanced across intrinsic, academic, career-oriented, and cross-cultural factors, with no single dominant factor. This indicates that course selection decisions are shaped by integrated motivational dimensions rather than isolated variables. This study contributes to educational research by providing an empirical and structured model of student motivation using PCA, offering a data-driven foundation for designing more responsive and contextually relevant Indonesian language curricula. Pemilihan mata kuliah Bahasa Indonesia dalam program studi non-bahasa seringkali dianggap sebagai kewajiban kurikuler, sehingga pemahaman tentang struktur motivasi yang mendasarinya menjadi terbatas. Kurangnya pemetaan empiris ini dapat menyebabkan desain kurikulum dan strategi pembelajaran yang tidak efektif. Oleh karena itu, penelitian ini bertujuan untuk mengidentifikasi dan menganalisis faktor-faktor motivasi yang memengaruhi pemilihan mata kuliah Bahasa Indonesia di kalangan mahasiswa Studi Asia Tenggara di Universitas Terbuka Ho Chi Minh City menggunakan Analisis Komponen Utama (PCA). Penelitian ini menggunakan pendekatan kuantitatif dengan desain analisis faktor eksploratori. Data dikumpulkan melalui kuesioner tertutup yang diberikan kepada 33 mahasiswa BIPA tingkat B1. Analisis data melibatkan pengujian kecukupan sampel (KMO), Uji Sferisitas Bartlett, ekstraksi komponen utama, dan rotasi faktor untuk mengidentifikasi struktur motivasi laten. Hasil penelitian menunjukkan bahwa motivasi mahasiswa bersifat multidimensional dan relatif seimbang di seluruh faktor intrinsik, akademik, berorientasi karir, dan lintas budaya, tanpa satu faktor dominan pun. Hal ini menunjukkan bahwa keputusan pemilihan mata kuliah dibentuk oleh dimensi motivasi yang terintegrasi, bukan variabel yang terisolasi. Studi ini berkontribusi pada penelitian pendidikan dengan menyediakan model empiris dan terstruktur tentang motivasi siswa menggunakan PCA, menawarkan landasan berbasis data untuk merancang kurikulum bahasa Indonesia yang lebih responsif dan relevan secara kontekstual.